Synthesis, biological evaluation, and utility of fluorescent ligands targeting the μ-opioid receptor - Schembri, Luke S.; Stoddart, Leigh A.; Briddon, Stephen J.; Kellam, Barrie; Canals, Meritxell; Graham, Bim; Scammells, Peter J. (American Chemical Society, 2015)
Fluorescently labeled ligands are useful pharmacological research tools for studying receptor localization, trafficking, and signaling processes via fluorescence imaging. They are also employed in fluorescent binding assays. This study is centered on the design, synthesis, and pharmacological evaluation of fluorescent probes for the opioid receptors, for which relatively few non-peptidic fluorescent probes currently exist. The known μ-opioid receptor (MOR) partial agonist, buprenorphine, was structurally elaborated to include an amidoalkylamine linker moiety that was coupled with a range of fluorophores to afford new fluorescent probes. All compounds proved to be selective MOR antagonists. Confocal fluorescence microscopy studies revealed that the probe incorporating a sulfonated cyanine-5 fluorophore was the most appropriate for imaging studies. This ligand was subsequently employed in an automated fluorescence-based competition binding assay, allowing the pKi values of several well-known opioid ligands to be determined. Thus, this new probe will prove useful in future studies of MOR receptor pharmacology.